2011
DOI: 10.1159/000331204
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of 10% α-Hydroxy Acid Emulsion on Skin pH

Abstract: Background/Aims: The effects of a 10% α-hydroxy acid (AHA) oil/water (O/W) emulsion on the pH of human skin surface (pHss) and stratum corneum (SC; pHsc) were evaluated in vivo. Methods: The AHA O/W emulsion was applied to an area on the volar forearm of male volunteers (n = 12), and then wiped off after 10 min. Prior to application and over the following 3 h, the pHss was measured. We used glass electrode measurements and time domain dual lifetime referencing (tdDLR) with lumi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Lactic acid could be synthesized by reduction of pyruvic acid or transformation of malic acid. Detected concentrations of succinic, malic, tartaric and lactic acids in investigated samples EW and EM might indicate that these acids might be responsible for the efficiency of cosmetic cream EM .…”
Section: Resultsmentioning
confidence: 99%
“…Lactic acid could be synthesized by reduction of pyruvic acid or transformation of malic acid. Detected concentrations of succinic, malic, tartaric and lactic acids in investigated samples EW and EM might indicate that these acids might be responsible for the efficiency of cosmetic cream EM .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to previous studies investigating a pH 4 O/W emulsion [15], the effect on pH SS of a pH 4 W/O emulsion was investigated regarding the acidifying properties. The two different emulsion types (W/O and O/W) exhibit different properties and thus differ with respect to influencing the pH SS .…”
Section: Discussionmentioning
confidence: 99%
“…glycolic acid)-containing O/W formulations are widely used in cosmetics and dermatology [14]. In a previous study, we showed that the application of a 10% glycolic acid-containing O/W emulsion with pH 4 reduced not only the pH SS but also led to a significant decrease of the pH in deeper layers of the SC (pH SC ), very likely even affecting the stratum granulosum [15]. …”
Section: Introductionmentioning
confidence: 99%
“…A significant reduction of the baseline pH ss could potentially be achieved by a longer application period or an O/W emulsion with a more acidic pH, like in previous studies [22,23]. …”
Section: Discussionmentioning
confidence: 90%
“…Several target groups that may profit from these products in particular have been defined in other studies (e.g., elderly, patients with atopic dermatitis, diabetics) [14,15,19,20,21,22]. Prior research of our study group examined the effect of a pH 4 water-in-oil (W/O) emulsion as well as a 10% α-hydroxy acid O/W emulsion on pH ss and pH sc in healthy subjects and diabetics [19,23]. …”
Section: Introductionmentioning
confidence: 99%